Penyuluhan Kesehatan Dan Deteksi Dini Penyakit Jantung Koroner Dengan Pemeriksaan Rekam EKG (Elektrokardiogram) di Muara Angke Kel. Pluit, Kec. Penjaringan - Zaenal Zaenal; Rahmat Pannyiwi; Meillisa Carlen Mainassy; Kurniati Nawangwulan; Yusnita Yusfik; Rizki Andita Noviar; M. Khalid Fredy Saputra (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Coronary Heart Disease is an atherosclerotic disease of an inflammatory nature, manifested by stable angina, unstable angina, myocardial infarction (MI), or sudden cardiac death. Symptoms that can arise from Coronary Heart Disease include chest pain, shortness of breath, heart attacks, changes in heart rate, nausea and extreme fatigue. The aim of community service is to evaluate and find the causes of health problems related to heart disease such as chest pain, fatigue, difficulty breathing and dizziness. Know the heart rhythm so you can detect if there is an irregular heart rhythm. The methods used in community service are health education and early detection of coronary heart disease by examining ECG (Electrocardiogram) records. The results of examination of ECG records from 15 residents, 3 people had normal ECG rhythms and 13 people had abnormal ECG rhythms with varying abnormalities. The conclusion is that there are still several risk factors in the group that need to be evaluated, such as smoking, diabetes mellitus, physical activity, family history and blood cholesterol levels.